LEGAL PROTECTION OF BANKRUPT CREDITORS AGAINST TRANSFER OF MANAGEMENT RIGHTS OVER LAND OWNED BY BANKRUPT DEBTORS DUE TO DELAY IN EXTENSION OF BATAM AUTHORITY'S ANNUAL MANDATORY MONEY - Sitindaon, Anggra Satria; Hadiyanto, Alwan; Anugrah Bhakti, Rizki Tri (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
When the soil entered estate bankruptcy, it experienced delays in paying the Batam Authority's Annual Mandatory Fee. The Batam Authority's Annual Mandatory Payment is one of the strongest pieces of evidence indicating that the company has legal ownership over the land. However, the possibility of the land being taken over by the Batam Business Agency is because the Batam Business Agency has the right to do so. However, the conflict of regulations that occurred also resulted in a legal vacuum, leaving a gap in resolving the problem. In this study, several issues are studied, including: How are the regulations regarding assets owned by bankrupt debtors, the rules regarding the transfer of land management rights by the Batam Business Agency, how the legal protection of bankrupt creditors regarding the transfer of land management rights owned by bankrupt debtors due to delays in extending the Batam Authority's annual mandatory money. The form of this research is normative legal research, utilizing secondary data as its primary source of information. The data analysis used is qualitative descriptive analysis. The assets owned by debtors who are declared bankrupt include those that already existed at the time of the bankruptcy decision, as well as those acquired during the bankruptcy process, referred to as estate bankruptcy. The supervisory judge and curator manage the estate in bankruptcy, with the results then distributed according to the previously determined repayment priorities. The transfer of land management rights can be carried out by BP Batam if several conditions are met, namely that the Batam Authority Annual Compulsory Money has not been paid or extended, there is a mismatch in land use, or the land has been given in not cultivated within a specific period. The transfer of management rights can be carried out because BP Batam is the holder of the management rights to the land in Batam. In facing the challenges faced by bankrupt creditors, legal protection is an essential aspect. One way to protect creditors is to strengthen the monitoring mechanism for the transfer of land management rights. Additionally, legal education for creditors needs to be improved so that they understand their rights within the bankruptcy process. Many creditors are not aware that they have the right to file objections to the transfer of management rights carried out by BP Batam. By improving legal understanding, creditors can be more proactive in protecting their rights.